Biologic aspects of different species of Pachodynerus (Hymenoptera; Vespidae; Eumeninae) - Buschini,MLT. (2010)
The aim of this study was to compare biological aspects of the Pachodynerus species occurring in the Parque Municipal das Araucárias, Guarapuava, Paraná, Southern Brazil. It was carried from December 2001 to December 2004. Forty one nests belonging to 5 species were collected, of which 17 Pachodynerus guadulpensis, 15 Pachodynerus sp., 1 Pachodynerus argentinus, 1 Pachodynerus ca guadulpensis and 7 Pachodynerus nasidens. The nesting activity of Pachodynerus sp., P. argentinus and P. guadulpensis occurred in similar periods, from December to March, with the exception of P.guadulpensis, that built one nest in October. Pachodynerus ca guadulpensis nested in March and P. nasidens from January to April. The nests of Pachodynerus species present a very similar architecture, comprising a linear series of cylindrical cells that fit perfectly into each other forming a continuous tube. With these results we were able to conclude that, even though Pachodynerus species present common characteristics, such as nest architecture, nesting activities and habitats in which they occur, the used resources, mortality rates, etc., vary among groups of species occurring in different regions.